Perjanjian Anjak Piutang Internasional - Nazarudin Nazarudin (Jurnal Hukum IUS QUIA IUSTUM, 2002)
Basically, the thrust of international credit is the same as domestic thrust credit Their differences are theparties involved more so that the contract they made is more complect, the timeis longer, there is guarantee of credit taking and the difference of countries. The Parties must be criticized carefully although in general the thrust of international credit need a board arbitration on solution for dispute.